Sludge-derived hydrochar and hydrothermal liquor enhance methane recovery and reshape antibiotic resistance gene mobility during sludge anaerobic digestion - Cheng Peng; Tianfeng Wang; Huiping Zhou; Xiangting Shi; Chenxi Zhang; Jinghan Zhang; Lijun Pu; Lanlan Qin; Qingfang Zhang; Xia Zhao; Huixia Feng (Bioresource Technology, 2026)

A novel method of determining optimal GNSS station density for NWP - Qingzhi Zhao; Qingfang Chen; Yongjie Ma; Haojie Li; Anbang Wu; Ming Liu; Yibin Yao; Hong Liang; Hongwu Guo; Yuxing Zhao; Jing Yang; Qingyuan Guo; et al. (Advances in Space Research, 2026)

Construction of photothermal hydrogel with sunlight internal reflection function for improving solar seawater evaporation efficiency - Shenghua Lv; Ying Chen; Shida Zhao; Wei Liu; Qingfang Zhou; Ruijun Gao (Chemical Engineering Journal, 2026)

Monoatomic copper anchored on tubular carbon nitride with high carbon/oxygen abundance via 2-methylimidazole direction: synthesis and catalytic performance - Jianghe Chen; Qingfang Zhang; Xia Zhao; Tianfeng Wang; Yabin Li; Zuoyan Chen; Wenjing Xu; Linhai Yang (Environmental Geochemistry and Health, 2026)

Correction: Sun et al. Tectonic Controls on Late Paleozoic Shale Gas Preservation in Western Shandong, China. J. Mar. Sci. Eng. 2025, 13, 1121 - Jing Sun; Yuting Zhao; Jie Liang; Xiujuan Zhang; Qingfang Zhao (Journal of Marine Science and Engineering, 2025)
Error in Figure/Table [...]

From biodegradation to biohazard: Polylactic acid microplastics induced rice growth inhibition in agroecosystems - Bigui Lin; Qingfang Fan; Fang Liu; Luya Wang; Chaoxian Wei; Beibei Liu; Juan Zhao; Linzi Zuo; Yi Xie (Journal of Hazardous Materials, 2025)

Adaptive fertilization strategies for premature senescence challenges in film-mulched maize: Insights from a 4-year field study - Haixiang Xiong; Chi Ma; Shujie Sun; Ziyi Wang; Ji Zhao; Chun Zhang; Lin Yang; Zhaoyun Dong; Zhikuan Jia; Dan Liu; Qingfang Han; Xudong Zhang (European Journal of Agronomy, 2025)

Tectonic Controls on Late Paleozoic Shale Gas Preservation in Western Shandong, China - Jing Sun; Yuting Zhao; Jie Liang; Xiujuan Zhang; Qingfang Zhao (Journal of Marine Science and Engineering, 2025)
Based on structural geology, petrology, shale gas geology, and basin modeling, this study investigates the characteristics of tectonic evolution and sedimentary responses in Western Shandong since the Late Paleozoic. Additionally, this study systematically investigates the hydrocarbon generation and reservoir formation conditions of Late Paleozoic shale gas and analyzes the controlling effects of tectonic activities on shale gas preservation. It is concluded that the TOC of the Late Paleozoic source rocks in this area ranges from 1.0% to 4.5%, considered as moderate to good source rocks. The Ro ranges from 0.7% to 3.5%, indicating a low to overmature stage. Deep concave source rocks have strong hydrocarbon generation potential. The Late Paleozoic shale gas reservoirs in Western Shandong are affected by superposed multiphase tectonic movements, where the activity of fault systems exerts dual controls on shale gas preservation.

Structural characterization of modified straw combined with CPAM conditioned sludge filter cake and analysis of its structure-performance relationship with sludge dewatering performance - Qiyong Yang; Yanbin Zhao; Qingfang Zhang; Ji Wang; Bingjie Xu; Xinhua Zhang; Houfeng Xiong; Han Zhou; Ruimin Xiao (Journal of Environmental Chemical Engineering, 2025)

Geochemical Tracing of Seabed Hydrocarbon Seepage in the Yantai Depression, South Yellow Sea Basin - Jianqiang Wang; Yuxi Zhang; Jian Zhang; Jie Liang; Qingfang Zhao; Heping Dong (Journal of Marine Science and Engineering, 2024)
Widespread submarine hydrocarbon seepage can form complex fluid seepage characteristics, with submarine sediment geochemistry effectively recording seepage activities and fluid component changes due to hydrocarbon seepage. This is crucial for offshore oil and gas exploration and understanding global climate change. Therefore, using the geochemical information of submarine sediments to trace hydrocarbon seepage activities is of great significance. In order to identify the geochemical anomaly characteristics and genetic types of acid-hydrolyzed hydrocarbons in submarine sediments in the Yantai Depression of the South Yellow Sea Basin, Eastern China, and to explore the relationship between these anomalies and deep oil and gas, geochemical columnar samples were taken at 100 stations in the study area. A total of 100 sets of acid-hydrolyzed hydrocarbon data and 26 sets of carbon isotope data were analyzed. The results show that the content of acid-hydrolyzed hydrocarbons at each station is in the following order: methane (AC1) > ethane (AC2) > propane (AC3) > butane (AC4) > pentane (AC5). The determination coefficient between the saturated hydrocarbon indicators exceeds 0.9, indicating that these components have the same source. Data analysis reveals that the genetic type of hydrocarbon gases in the study area is generally thermogenic, with limited microbial contribution to saturated hydrocarbons, indicating deep oil and gas characteristics. The coincidence between the anomalous areas and geological structures indicates that the distribution of these anomalies is closely related to fault distribution.

Fault Characteristics and Reservoir Potential of Mesozoic Basins in the Southern East China Sea - Yanqiu Yang; Chuansheng Yang; Jing Sun; Jie Liang; Qingfang Zhao; Jianqiang Wang (Journal of Marine Science and Engineering, 2024)
The East China Sea Basin (ECSB) is an integral part of the Western Pacific tectonic system. Its development is linked to the Kula–Pacific Plate and the formation and expansion of the Philippine Sea Basin. Recent advancements in exploration technologies and theory have been applied to Mesozoic basins in the East China Sea. Researchers have posited that the southern basin has great oil and gas exploration potential. However, the characteristics and evolution of fault structures and their influence on hydrocarbon accumulation remain unclear. Here, in-depth geometric and kinematic analyses of Mesozoic fault structures in the southern ECSB were conducted using the latest interpretations of 2D seismic data and structural analysis theory. The findings revealed that the fault system was well developed and predominantly exhibited multiphase extensional and extensional-torsional features. Based on their lateral distribution and morphology, faults were categorized into three structural styles and seven combinations. According to their developmental timing, periods of active faulting were attributed to the Yanshan and Himalayan epochs. Multiphase fault activities strongly controlled the formation of traps and thus hydrocarbon accumulation, while earlier NE-trending faults controlled the formation of structural belts and hydrocarbon source areas.

Enhancement of alkaline pretreatment-anaerobically digested sludge dewaterability by chitosan and rice husk powder for land use of biogas slurry - Tianfeng Wang; Ziying Xu; Hailong Shi; Yanbin Zhao; Wenqi Gao; Yuanshun Xu; Qingfang Zhang (Journal of Environmental Management, 2024)

The Volcanic Rocks and Hydrocarbon Accumulation in the Offshore Indus Basin, Pakistan - Jing Sun; Jie Liang; Jianming Gong; Jing Liao; Qingfang Zhao; Chen Zhao (Journal of Marine Science and Engineering, 2024)
To analyze the impact of volcanic rocks in the Offshore Indus Basin on hydrocarbon reservoir formation, seismic data interpretation, seismic data inversion, and sea–land correlation analysis were carried out. The results show that, longitudinally, volcanic rocks are mainly distributed at the top of the Cretaceous system or at the bottom of the Paleocene, and carbonate rock platforms or reefs of the Paleocene–Eocene are usually developed on them. On the plane, volcanic rocks are mainly distributed on the Saurashtra High in the southeastern part of the basin. In terms of thickness, the volcanic rocks revealed by drilling in Karachi nearshore are about 70 m thick. We conducted sparse spike inversion for acoustic impedance in the volcanic rock area. The results show that the thickness of the Deccan volcanic rocks in the study area is between 250 and 750 m which is thinning from southeast to northwest. Based on sea–land comparison and comprehensive research, the distribution of volcanic rocks in the Indian Fan Offshore Basin played a constructive role in the Mesozoic oil and gas accumulation in the Indus offshore. Therefore, in the Indian Fan Offshore Basin, attention should be paid to finding Mesozoic self-generated and self-stored hydrocarbon reservoirs and Cenozoic lower-generated and upper-stored hydrocarbon reservoirs.

Recovery and characterization of β-glucosidase-producing non-Saccharomyces yeasts from the fermentation broth of Vitis labruscana Baily × Vitis vinifera L. for investigation of their fermentation characteristics - Ling Zhu; Xuemei Zhang; Yuchen Wang; Xiu Gao; Qingfang Xu; Weiliang Liu; Qihe Xu; Dongmei Zhao; Jian Cai (Archives of Microbiology, 2024)

Effects of chitosan and rice husk powder on thermal hydrolysis-anaerobic digested sludge conditioning: Dewaterability and biogas slurry fertility - Qingfang Zhang; Hailong Shi; Yanbin Zhao; Jiajia Pu; Cheng Peng; Ruoyu Wu; Yuqian Zhang; Ziying Xu; Tianfeng Wang (Chemosphere, 2024)

Characterization of a Saccharum spontaneum with a basic chromosome number of x = 10 provides new insights on genome evolution in genus Saccharum - Zhuang Meng; Jinlei Han; Yujing Lin; Yiyong Zhao; Qingfang Lin; Xiaokai Ma; Jianping Wang; Muqing Zhang; Liangsheng Zhang; Qinghui Yang; Kai Wang (Theoretical and Applied Genetics, 2020)

Tanning performance and environmental effects of nanosized graphene oxide tanning agent - Shenghua Lv; Qingfang Zhou; Ying Li; Yaya He; Haoran Zhao; Shiyu Sun (Clean Technologies and Environmental Policy, 2016)

Tree-scale spatial variation of soil respiration and its influence factors in apple orchard in Loess Plateau - Rui Wang; Shengli Guo; Jishao Jiang; Defeng Wu; Nana Li; Yanjun Zhang; Qingfang Liu; Rujian Li; Zhiqi Wang; Qiqi Sun; Lanlan Du; Man Zhao (Nutrient Cycling in Agroecosystems, 2015)

Determination of zinc contents in rabbits with cerebral ischemia by NAA and ICP-AES - Yinsong Wang; Huifang Zhao; Tianxi Zhang; Mingguang Tan; Guisun Zhuang; Baolin Chen; Zongzhi Huang; Hengli Tian; Qingfang Sun (Biological Trace Element Research, 1999)